Peran Pembelajaran Tematik dalam Meningkatkan Keaktifan dan Pemahaman Siswa Sekolah Dasar: Systematic Literature Review - Agus Dwi Prasojo; Nur Aisyah; Nur Fazriah Rahmawati; Wulan Ramadhani; Windri Efina Baihaqi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Thematic instruction in elementary education integrates multiple subject areas under a common theme to promote meaningful learning experiences. This study examines the relationship between thematic learning, student engagement, and conceptual understanding in elementary schools using a Systematic Literature Review (SLR). A total of 20 Indonesian journal articles published between 2020 and 2025 were selected based on predefined inclusion criteria and analyzed thematically. The findings reveal that thematic learning increases student engagement through interactive discussions, inquiry-based learning, and collaborative activities. In addition, integrating different subject areas helps students develop deeper conceptual understanding by connecting learning with real-life contexts. The effectiveness of thematic learning is influenced by teachers’ competence in designing integrated instruction, selecting appropriate learning strategies, and utilizing relevant instructional media. Therefore, integrated thematic learning is an effective approach for improving both student engagement and conceptual understanding in elementary education.